Historical overview of public transit regulation in Lima - Poole Fuller, Esteban (2020)
The legal framework of public transit in Lima has undergone, over the course of its history, a complex evolution, along with the changing technological, social and urban conditions in which it has developed. In turn, both the social context and the legal framework of this activity have been undergoing profound changes in recent years. In this sense, after several decades of intense deregulation and liberalization of public transit services, a set of measures has been adopted to reorganize it under the framework of an Integrated Transit System (SIT), in which a public service legal regime is being reintroduced for the activity. These changes, however, exhibit tensions with the persistence of high levels of informality in public transit services. Given the importance of the changes that are currently taking place in the regulation of public transit and mobility in Lima, and the urgency to order them more rationally, arises the need to analyze the historical background of these dynamics and their legal framework. In view of this, this article aims to provide a historical overview of the evolution of public transit regulation in Lima from the issuance of the Municipal Carriage Regulation of 1874, the first general scope legal instrument regarding public transit in Lima, up to date. The article seeks to contribute to the understanding of the factors that have led to the current situation of public transit and urban mobility and to what extent legal factors have influenced it.